Technopreneurship Intention: A Study of Economic Education Study Program Students Influenced by Entrepreneurial Learning - Sudarwati, Ninik; Chalimah (Jurnal Pendidikan Indonesia, 2022)
The unemployment rate among educated people in Indonesia is increasing every year as the Central Statistics Agency noted that from 2016 to 2020 it was 7.35%. The increasing number of unemployed among the educated is supported by the fact that most university graduates prefer to be job seekers rather than job creators. This shows that the entrepreneurial intention of students is still low, so entrepreneurship learning is needed to grow technopreneurship intentions. This study aims to analyze the effect of entrepreneurial learning on students' technopreneurship intention. This is an explanatory survey conducted using questionnaires to collect data followed by testing of hypothesis and analyzing the data through the regression technique. The population involved 112 students and a saturated sample was used. The results showed that the overall student entrepreneurial learning is effective and student technology-based business activities are high. Moreover, the entrepreneurial learning variable was found to affect students' technology-based business activities. This implies it is necessary to increase entrepreneurial learning by participating deeply in industry, recognizing opportunities through cultural participation, and applying the practical theory of entrepreneurial action to increase the technopreneurship intention of students.